The Common Table, no. 5 (Spring 2022) - Schieferstein, Mary; DeJong, Brendan; Augustine, David; Preib, Bailey; Vining, Rachel (2022)
The Study Table -- Who Needs a Spiritual Life? -- An Israelite Education for the Church -- Narratives of the Black Taboo: Suicide Excerpt -- Climate Change and the Church -- Easter: God’s Answer to Injustice -- Western Affluence and Refugees -- On Choice from a Collective Lens -- The Art Table -- The Sunset -- Immutable -- Olmos Park-itecture -- The Family Madrigal: Family Systems in Disney’s Encanto -- The Second Greatest Commandment -- Holy Saturday: Peter’s Wife -- Betrayal and Trial -- Spiderwebs -- The Community Table -- Professor Profile: Mike Higgins -- Professor Profile: Jerram Barrs -- Photos of Flowers -- Mike Higgins Reflections and Quotes -- Jerram Barrs Reflections and Quotes